(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Building design and space morphology strongly impact the life and structure of a community .Urban form is an outcome of human activity and thus it has a strong impact on social interaction, which isassumed to be one of the major design elements in urban planning. Apart from providing a living spacefor the inhabitants, housing should also offer spaces for community life to develop and nurture . Spatialorganization in a residential neighbourhood is thus a strong indicator of a region and its varied socialsetups. In present times, majorly after 1990”s, rapid urbanization and borrowed western ideas gave birthto prototypical high rise developments as part of mass housing. Aim behind such growth was to fulfil theover growing need of housing in urban areas. Vernacular ideas have been replaced by modernist spacesthat eventually lead to a development which had no connection with the environment and the peoplearound. Designers and planners, very conveniently, had ignored the significance of human scale and thepeople who are the actual end users. Factory made neighbourhood and residential colonies wereplanned that lack identity and interaction centric spatial organization. Gradually, traditional residentialareas having intense connection with man and surrounding and possess strong connections have beenreplaced by fragmented and introvert setups. Building such neighbourhoods is a challenge in presenttimes. No solution can be considered perfect in such a situation. This paper thus attempts to analyse theconnection between spatial layout and urban form with social relations towards forming a sociallycohesive society. It tries to establish a relationship between sociocultural aspects of a society andspatial geometry in terms of morphology and design process. With the help of a comparative study donethrough field surveys from certain selected neighbourhoods of Walled city of Jaipur and a newly formedresidential neighbourhood of southern Jaipur, this study is an attempt to document and comprehend arelationship between the geometry of built environment with human behaviour w.r.t the spaces designedfor them.